Molecular-level analysis of the wetting behavior of imidazolium-based ionic liquids on bismuth telluride surfaces. (16th January 2020) - Atkinson, Henry; Bara, Jason E.; Turner, C. Heath
Graphical abstract: Highlights: Ionic liquid contact angles on bismuth telluride are computationally predicted. Contact angles are strongly dependent on the ionic liquid anion. Atom ordering near bismuth telluride surface is strongly correlated to contact angle. Simulations provide insights for selecting solvents for exfoliating 2D materials. Abstract: Bismuth telluride is among the most studied thermoelectric materials. Its performance, which is among the highest around room temperature, is dependent on exfoliation to thin nanosheets. While previous research has examined the exfoliation mechanism by ionic liquids (ILs), this study provides more detailed information about the solid-liquid interface, including predicted values for IL contact angles ( θ ) on Bi2 Te3 . Molecular dynamics simulations are employed to compute θ and other properties of interest, including mass and charge ordering, adsorption energy, and electrostatic potential. All properties save the latter are strongly dependent on anion size and slightly dependent on cation size. The IL contact angles display a wide range of values, from 97.7° for the smallest ions to 53.2° for the largest ions. An analysis of the molecular-level interactions in these systems serves to explain this behavior, and they indicate that reduced cohesive interactions in bulkier liquids are primarily responsible.